Optimizing the Role of Kiai in Preparing Competitive Santripreneurs - Hidayat, Ahmad Agus; Buchori, Imam; Arlina, Agustin Mila; Muflihin, Mohammad Dliyaul; Ashari, Muhammad Rizki (Islamic Economics Journal, 2024)
Pesantren economics has increasingly gained attention from various circles, moving away from the traditional stigma of being solely traditional educational institutions. This article explores the role of the Kiai of Darul Pesantren, Menganti, in developing and preparing santripreneurs. This article employs qualitative research with a case study approach. Use the triangulation method. Data analysis was conducted through data reduction, data presentation, and verification. The validity of the findings was ensured through extended observation and methodological triangulation. The study's findings reveal that the role of the Kiai in preparing santripreneurs is carried out through several methods: a) Doctrination of students through the learning process, b) Aligning student's areas of expertise with their interests and talents, c) Establishing partnerships and collaborations with third parties, d) Incorporating santripreneurs education into extracurricular activities at the pesantren, e) Providing educational scholarships for students, f) Requiring all students to have savings in the pesantren through BMT (Baitul Maal wa Tamwil). On the other hand, the challenges faced include: a) A lack of motivation among students to learn entrepreneurship, b) Time constraints for both students and instructors, c) Limited entrepreneurial capital, and d) A shortage of human resources within the pesantren.